Long Non-coding RNA MIR570MG Causes Regorafenib Resistance in Colon Cancer by Repressing miR-145/SMAD3 Signaling - Wei, Fang; Wang, Mofei; Li, Zhen; Wang, Yong; Zhou, Yong (Frontiers in Oncology, 2020)
An increasing number of studies have shown that long non-coding RNA (lncRNA) dysregulation plays a fundamental role in the development of various cancers, including colon cancer. Nonetheless, the mechanisms of lncRNA in regorafenib-resistance remain unclear. Our research revealed the lncRNA MIR570MG increased in regorafenib-resistant colon cancer cells compared to the regorafenib-sensitive cells. Furthermore, MIR570MG sponged miR-145, which declined in regorafenib-resistant colon cancer cell lines. More importantly, overexpression of miR-145 hampered cell proliferation and retrieved colon cancer regorafenib-sensitivity, contrary to the function of MIR570MG. Dual-luciferase reporter assay confirmed that miR-145 bound to 3′-UTR of SMAD3, a transcriptional modulator activated by TGFβ, resulting in blockage of TGFβ /SMAD3-mediated cell growth and cycle progression. Besides, ectopic expression of miR-145 inhibitor in the parental cells endowed resistance to regorafenib. Inversely, knockdown of MIR570MG impoverished resistance against regorafenib. Additionally, overexpression of MIR570MG conquered the suppression of tumor growth by miR-146 and rehabilitated the resistance to regorafenib in HCT116R human colon cancer mouse models. In summary, our findings suggested that MIR570MG promoted regorafenib resistance via releasing SMAD3 from miR-145, leading to activation of SMAD3-mediated signaling pathways.